PENGARUH IMPLEMENTASI TARIF INTEGRASI, STRATEGI PEMASARAN DAN PENGETAHUAN PENGGUNA TARIF INTEGRASI TERHADAP LOYALITAS PELANGGAN PENGGUNA ANGKUTAN UMUM DI DKI JAKARTA - Kusumawardani, Ratih; Yenita, Yenita (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2023)
Comprehensive integration services, on mass public transportation services operated by the DKI Jakarta Provincial Government carried out by PT. Jaklingko. The quality of service for the integration of fares and tickets in the integration of the transportation systemhas not been in line with user expectations. This study aims to examine the role of integrated tariffs, marketing strategies and knowledge of public transportation users in relation to the loyalty of public transportation use. Data obtained using the survey method conducted online to users of public transportation services in DKI Jakarta which wasdeveloped as a hierarchical component using a reflective-reflective measurement model and assessed using PLS-SEM, the results showed that the variables were found to have a positive and significant correlation. Research also proves that with the integras i tariff policy on public transportation , a good marketing strategy and knowledge of public transportation users can affect the loyalty of public transportation users in DKI Jakarta.